Lnk Deficiency Leads to TPO‐Mediated Osteoclastogenesis and Increased Bone Mass Phenotype. Issue 8 (18th April 2017) - Olivos, David J.; Alvarez, Marta; Cheng, Ying‐Hua; Hooker, Richard Adam; Ciovacco, Wendy A.; Bethel, Monique; McGough, Haley; Yim, Christopher; Chitteti, Brahmananda R.; Eleniste, Pierre P.; Horowitz, Mark C.; Srour, Edward F.; et al.
ABSTRACT: The Lnk adapter protein negatively regulates the signaling of thrombopoietin (TPO), the main megakaryocyte (MK) growth factor. Lnk‐deficient (−/−) mice have increased TPO signaling and increased MK number. Interestingly, several mouse models exist in which increased MK number leads to a high bone mass phenotype. Here we report the bone phenotype of these mice. MicroCT and static histomorphometric analyses at 20 weeks showed the distal femur of Lnk −/− mice to have significantly higher bone volume fraction and trabecular number compared to wild‐type (WT) mice. Notably, despite a significant increase in the number of osteoclasts (OC), and decreased bone formation rate in Lnk −/− mice compared to WT mice, Lnk −/− mice demonstrated a 2.5‐fold greater BV/TV suggesting impaired OC function in vivo. Additionally, Lnk −/− mouse femurs exhibited non‐significant increases in mid‐shaft cross‐sectional area, yet increased periosteal BFR compared to WT femurs was observed. Lnk −/− femurs also had non‐significant increases in polar moment of inertia and decreased cortical bone area and thickness, resulting in reduced bone stiffness, modulus, and strength compared to WT femurs. Of note, Lnk is expressed by OC lineage cells and when Lnk −/− OC progenitors are cultured in the presence of TPO, significantly more OC are observed than in WT cultures. Lnk is also expressed in osteoblast (OB) cells and in vitro reduced alkaline phosphatase activity was observed in Lnk −/− cultures. These data suggest that both direct effects on OB and OC as well as indirect effects of MK in regulating OB contributes to the observed high bone mass. J. Cell. Biochem. 118: 2231–2240, 2017. © 2017 Wiley Periodicals, Inc. Abstract : The LNK adapter protein negatively regulates the signaling of thrombopoietin (TPO), the main megakaryocytic growth factor. LNK deficient mice have enhanced TPO signaling, increased megakaryocyte number which leads to osteoblast proliferation, and osteoclast differentiation resulting in a high bone mass phenotype.